Rigidity and fuzziness within the framework of English Statutes and Law Reports. Original French title: Rigidité et Fluidité dans les cadres Législatif et jurisprudentiel anglais - Wagner, Anne (International Journal of Speech, Language and the Law, 2001)
The thesis uses a substantial corpus which spans a period of 100 years toexamine English legal discourse and the appropriateness of law as a specializedlanguage and as a linguistic medium. The analysis has three mainfoci: (1) the analysis of the message content by means of refining the techniquesof semioticians and linguists, (2) the study of English history and itsinfluence on the language of English law and (3) the technical and specializedcontributions of jurists and judges (from the civil, theadministrative or the criminal register). Two layers within the discourseare then distinguished in this study: rigidity and fluidity which show a permanencyand renewal.A major concentration in the study is vocabulary relations. Legal wordshave a peculiar tenacity – an ability to achieve stability within changingsocial and economic conditions (Gény 1922) although the illusion is ofconservatism, rigidity and uniformity – because the social structure penetratesinto the architecture of legal language. That is why every past andpresent society has its own knowledge of words, and many have creatednew words or modified the meanings of existing words in order to reflecttheir particular standards and expectations (Hobbes 1971), as shownbelow for the word ‘night’: Under the Night Poaching Act 1828, s.12, it is stated that “the nightshall be considered and is hereby declared to commence at the expirationof the first hour of sunset, and to conclude at the beginning ofthe last hour before sunrise”. Under the Customs and Excise Management Act 1979, s.1 “night meansthe period between 11 p.m. and 5 a.m.”. Under the Highways Act 1980, s.329(1) it “means the time between halfan hour after sunset and half an hour before sunrise”.Moreover, this web-like semantic organization – described by Eco (1976)as a multi-levelled maze – demonstrates complexity which arises from thespecific activities of professionals (either judges, jurists or MPs) whoimpose their definitions and contributions upon historical, economic andsocial events showing, for example, a conflict with the contemporarygrammar: In any Act, unless the contrary intention appears, (a) words importing the masculine gender include the feminine; (b) words importing the feminine gender include the masculine; (c) words in the singular include the plural and words in the pluralinclude the singular. (Interpretation Act 1978, s.6)Therefore, it is highly important to show how lexical items, created ormodified by jurists, judges and MPs, slot into the common language andhow the factual references turn the semantic content into a technical language:history, aspects of generalization (‘dis-individual’ in Delmas-Marty1986: 25), judicial actors and formal systems have an influence over themeanings of legal terms. One more obvious and important point emerges; that text-organizingvocabulary (Coltier and Turco 1988) functions on the surface of some specificgenre discourses (Kevelson 1988, 1991). Three genre discourses areexamined: prescriptive, descriptive and explanatory registers. Theiranalysis demonstrates that the influence of judicial speech is, paradoxically,a source of both rigidity and fuzziness.Besides, this language of the law has developed in a social context,meaning that it will gradually change according to the social and historicalcircumstances of the country (Carbonnier 1978). Thus another genrefactor to be reckoned with is related to the difference between academicscience and popular science, i.e. professionals of the field and lay people.Indeed words have their own legal tradition (history) or silent backgrounds(specialized meanings) which can only be understood by aprofessional of the field. Given this criterion, lay individuals are in a stateof perplexity because the language of the law has developed withouttaking into account everybody’s personal background (‘a language of fool’in Gridel 1994). And so, there is a clear division between non-practisingpeople and practitioners as shown below with the word complainant: one who makes a complaint to the justices (Jowitt Dictionary)In subsection (1) of this section “complainant” means a woman uponwhom, in a charge for a rape offence to which the trial in questionrelates, it is alleged that rape was committed, attempted or proposed (Sexual Offences (Amendment) Act 1976, s.3)Moreover, English law still interlocks with other European Union membercountries’ legal architectures and will affect their future evolution. So, thelast issue highlighted in this thesis – ‘LSP translation’ – considers thatwords do not develop along the same path in all languages. Indeed, as languagesare influenced by the culture and the history they are part of (thefuzzy part), LSP translators must find acceptable words in the other languagein order to produce an acceptable translation. As a result they mustavoid mismatches between the source-language (Legal English) and thetarget language (Legal French). That is the reason why the primary task fortranslation consists in exploring the common territory where legal Englishterms and legal French words can work together and share the knowledgethat belong to both (the rigid part). The main aim of LSP translation willthen be to develop the ability of translators to perfectly comprehend bothEnglish and French legal reasoning, the nature of the subject, and thesubject treated, so that translators may express themselves as justly as ifthey wrote the original.REFERENCESAustin, J. L. (1970) Quand dire, c’est faire, Paris: Editions du Seuil.Carbonnier, J. (1978) Sociologie juridique, Paris: P.U.F.Coltier, D. and Turco, G. (1988) ‘Des agents doubles de l’organisationtextuelle: les marqueurs d’intégration linéaire’, Pratiques, 57: 40–60.Delmas-Marty, M. (1986) Le flou du droit, Paris: P.U.F.Eco, U. (1976) A Theory of Semiotics, Bloomington: Indiana UniversityPress.Gény, F. (1922) Science et Technique en Droit Privé Positif, Tome 1, Paris:Recueil Sirey.Goodrich, P. (1990) Languages of Law (from Logics of Memory toNomadic Masks), London: Weidenfeld & Nicolson.Gridel, J.P. (1994) Introduction au droit et au droit français, Paris: Dalloz.Halliday, M.A.K. (1978) Language As Social Semiotics, London: EdwardArnold.Hobbes, T. (1971) Léviathan, Paris: TricaudKevelson, R. (1988) Law as a System of Signs, London: Plenum.Kevelson, R. (1991) Action and Agency, New York: Peter Lang.Lerat, P. (1995) Les langues spécialisées, Paris: P.U.F.